Clinicopathologic features and biologic behavior of canine splenic nodules with stromal, histiocytic and lymphoid components - Sabattini, Silvia; Rigillo, Antonella; Foiani, Greta; Marconato, Laura; Vascellari, Marta; Greco, Alessandra; Agnoli, Chiara; Annoni, Maurizio; Melchiotti, Erica; Campigli, Michela; Benali, Silvia Lucia; Bettini, Giuliano (Frontiers in Veterinary Science, 2022)
The term fibrohistiocytic nodule has been discouraged in favor of specific pathologic entities, including complex nodular hyperplasia, splenic stromal sarcoma and histiocytic sarcoma. Nevertheless, the diagnosis of splenic lesions with mixed stromal, histiocytic and lymphoid components still remains a challenge due to lack of straightforward histologic criteria. Misestimation of the biologic behavior of these lesions may lead to detrimental consequences on the clinical management of patients. In this study, we retrospectively evaluated the clinicopathologic features and outcome of canine splenic nodular lesions with mixed components, to identify prognostic factors and histologic criteria of malignancy. Thirty-seven cases were included. Immunohistochemistry did not allow for further subclassification. Nine (24.3%) dogs died from disease-related causes after a median of 234 days (range, 48–1247). One-, 2- and 3-year disease-specific survival rates were 80%, 60% and 43%, respectively. When considering nodules with stromal cell atypia and at least one of mitotic count ≥9, presence of karyomegaly/multinucleated cells and lymphoid component <40%, half of these dogs died of disease-related causes with a median disease-specific survival time of 548 days (95% CI, 0-1216). In the remaining dogs, no disease-related death was reported (P < 0.001). Canine splenic nodular lesions with mixed stromal, histiocytic and lymphoid components and histologic criteria of malignancy may behave aggressively, leading to distant metastasis and death. In the absence of further criteria aiding their classification, and to better characterize their biologic behavior, we encourage the distinction of these complex splenic tumors from conventional sarcomas and histiocytic sarcomas.